2018
DOI: 10.1021/acs.jafc.7b05163
|View full text |Cite
|
Sign up to set email alerts
|

A Comparative Study on Formation of Polar Components, Fatty Acids and Sterols during Frying of Refined Olive Pomace Oil Pure and Its Blend Coconut Oil

Abstract: The frying performance of pure refined olive-pomace oil (ROPO) and blended with refined coconut oil (RCO) (80:20) was compared during a frying operation of French fries at 180 °C. Blending polyunsaturated oils with highly saturated or monounsaturated oils has been studied extensively, however in literature there is no study has been reported so far on blending ROPO (rich in monounsaturated fatty acids) with RCO (rich in saturated fatty acids) to formulate new frying oils. At the end of the frying process, the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
32
2
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 31 publications
(40 citation statements)
references
References 40 publications
5
32
2
1
Order By: Relevance
“…The fatty acids identified were palmitic acid (C16:0), stearic (C18:0), oleic (C18:1), linoleic According to our previous results [14], the data showed that the amount of PUFAs such as the linoleic and linolenic acids decreased gradually after 60 sessions of frying in both oils (ROPO pure and ROPO/RCO) ranging between 16.95% and 0.64%, respectively, whereas, varying between 12.94% and 0.40%, respectively. Consequently, a relative increase in the percentages of SFAs such as the palmitic acid was observed.…”
Section: Fatty Acid Compositionsupporting
confidence: 64%
See 3 more Smart Citations
“…The fatty acids identified were palmitic acid (C16:0), stearic (C18:0), oleic (C18:1), linoleic According to our previous results [14], the data showed that the amount of PUFAs such as the linoleic and linolenic acids decreased gradually after 60 sessions of frying in both oils (ROPO pure and ROPO/RCO) ranging between 16.95% and 0.64%, respectively, whereas, varying between 12.94% and 0.40%, respectively. Consequently, a relative increase in the percentages of SFAs such as the palmitic acid was observed.…”
Section: Fatty Acid Compositionsupporting
confidence: 64%
“…Blending the polyunsaturated oils with more saturated or monounsaturated oils is a potential solution to improve oil stability [14].…”
Section: Oil Samplesmentioning
confidence: 99%
See 2 more Smart Citations
“…PUFA is known to play a crucial role in human nutrition by preventing health disorders. Because palmitic acid is more stable against oxidation, whereas linoleic acid is more susceptible to oxidation, the C 18:2n6 /C 16:0 ratio may be an effective indicator of the degree of edible oil deterioration (Hammouda, Triki, Matthäus, & Bouaziz, 2018;Zribi, Jabeur, Matthäus, & Bouaziz, 2016). Additionally, palmitic acid level was increased after frying, which has been reported by Bansal et al (2010), who revealed that oxidative deterioration of linoleic acid under hightemperature condition led to the formation of palmitic acid.…”
Section: Fatty Acid Profile Of Frying Oilmentioning
confidence: 71%